Beyond shifting intergroup attitudes: Intergroup contact's association with socio‐cognitive skills and group‐based ideologies. (18th March 2019) - Bagci, Sabahat Cigdem; Piyale, Zeynep Ecem; Sen, Ezgi; Yildirim, Osman
Abstract: We investigated intergroup contact's cognitively liberalizing function by testing it's association with socio‐cognitive skills (perspective‐taking and empathy skills, and cognitive flexibility) and group‐based ideologies (ethnocentrism and social dominance orientation [SDO]) among a majority (Turks) and minority (Kurds) status group (total N = 483). We further examined whether these relationships were provided by contact's primary intergroup function—more positive attitudes toward the contacted group. Multigroup structural equation modeling analyses demonstrated that high quality cross‐group friendships were directly and negatively related to both ethnocentrism and SDO among the minority group. These associations were mediated by positive outgroup attitudes among the majority group. For both groups, perspective‐taking and empathy were significantly predicted by lower levels of ethnocentrism and SDO. Contact also indirectly led to higher cognitive flexibility among both groups. Findings highlight the need to explore more extensively contact's psychological outcomes at the individual level, beyond changing outgroup attitudes.